1994
DOI: 10.1111/j.1532-5415.1994.tb06982.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Treatment of Agitation in Nursing Home Patients with Dementia: A Preliminary Study

Abstract: This preliminary study suggests that carbamazepine in low doses can reduce agitated behaviors in some patients, with limited adversity resulting. Further research is required to confirm and extend this finding before it can be considered routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 38 publications
0
53
1
1
Order By: Relevance
“…Recommendations about the use of carbamazepine to treat aggression in elderly demented patients have been tempered by concerns about its potential to cause serious haematological sideeffects (Leong and Silva, 1988). There were no such adverse effects in our sample and indeed none reported in the previous case series involving 66 patients (Chambers et al, 1982;Patterson, 1988;Gleason and Schneider, 1990;Tariot et al, 1994). However, longer follow-up studies would clarify its safety over more prolonged periods of treatment.…”
Section: ' 8 9 17contrasting
confidence: 44%
See 1 more Smart Citation
“…Recommendations about the use of carbamazepine to treat aggression in elderly demented patients have been tempered by concerns about its potential to cause serious haematological sideeffects (Leong and Silva, 1988). There were no such adverse effects in our sample and indeed none reported in the previous case series involving 66 patients (Chambers et al, 1982;Patterson, 1988;Gleason and Schneider, 1990;Tariot et al, 1994). However, longer follow-up studies would clarify its safety over more prolonged periods of treatment.…”
Section: ' 8 9 17contrasting
confidence: 44%
“…Two previous placebo-controlled studies to assess the efficacy of carbamazepine in this context yielded conflicting results (Tariot et al, 1994;Chambers et al, 1982). Chambers et al (1982) reported a lack of efficacy of carbamazepine in their trial.…”
mentioning
confidence: 95%
“…Target symptoms in trials and in clinical practice have been primarily agitated or aggressive behavior, and not psychosis. Three controlled studies examined the effect of carbamazepine on symptoms of tension, hostility, uncooperativeness, or excitement in patients with advanced AD [81] or with AD or vascular dementia [82,83]. One study included outpatients who had previously not responded to neuroleptic treatment [81].…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…95 Carbamazepine was studied in the treatment of agitation and psychosis and reported benefits. 96 The antidepressant agent citalopram was proposed as a treatment for agitation in a poorly defined population with "cognitive deficits." 97 Depression.…”
Section: Ischemic Vascular Dementiamentioning
confidence: 99%